Houseflies (Musca spp.) in Pig Farming Systems: Implications for Health and Environmental Management in Tropical Indonesia - Quinthia Amanda Manitik; Meis Jacinta Nangoy; Wulan Pingkan Julia Kaunang; Jane Silvana Iriane Onibala; Juliet Merry Eva Mamahit; Jane Maria Fransiska Tahulending (CV. Science Tech Group, 2026)
Houseflies (Musca spp.) are common synanthropic insects in pig farming systems and are widely recognized for their potential role in the mechanical transmission of pathogens, particularly in tropical endemic settings. In Indonesia, pig farming is frequently conducted in close proximity to residential areas, where inadequate environmental management may increase risks to animal and public health. This study aimed to examine the presence and potential role of houseflies in pig farming systems and to assess their implications for health and environmental management in tropical Indonesia. A cross-sectional observational study was conducted in selected pig farming areas. Houseflies were collected using standardized trapping techniques from pig housing, waste accumulation sites, and surrounding environments. Microbiological analyses were performed to detect pathogenic bacteria associated with gastrointestinal and zoonotic diseases, while environmental management practices, including waste handling, sanitation, and biosecurity measures, were assessed through structured observations and interviews. The findings revealed high housefly density in areas characterized by poor waste management and suboptimal sanitation conditions. Pathogenic bacteria of public health significance were identified on the external surfaces of collected houseflies, indicating their potential role as mechanical vectors. Farms implementing better environmental management practices showed lower fly abundance and reduced levels of microbial contamination. These results underscore the importance of integrated health and environmental management in pig farming systems. Improving waste management, sanitation, and fly control measures is essential to reduce disease transmission risks and to support sustainable and health-oriented livestock production in tropical regions of Indonesia.